2019
DOI: 10.30772/qjes.v12i2.596
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Leachate Recirculation on Biological Stability of Municipal Solid Waste Under Simi-Arid Conditions

Abstract: A B S T R A C TThe present study was conducted to monitor the quality of leachate generated from solid waste landfills operated under different mode over a period of 335 days using a bench scale lysimeters. Sixty six kg waste sample reflecting the typical municipal solid waste (MSW) streams generated in Al-Diwaniyah city open dump was used to fill both sanitary and bioreactor lysimeters to study the influence of leachate recirculation on quality of leachate in landfills located in semi-arid areas. Leachate qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Abud et al focused on modifying leachate characteristics using a lime and sawdust waste mixture that assisted in enhanced solid waste stabilization [8]. In their research to examine the impact of leachate recirculation on the biological stability of MSW, Hussain, and Al-Ameen found that bioreactor landfills with leachate recirculation are superior to sanitary landfills at removing organic matter [9]. The amount of leachate and chemical composition, as well as the distance of the pollutant from the source of water, will affect the pollution level [10].…”
Section: Introductionmentioning
confidence: 99%
“…Abud et al focused on modifying leachate characteristics using a lime and sawdust waste mixture that assisted in enhanced solid waste stabilization [8]. In their research to examine the impact of leachate recirculation on the biological stability of MSW, Hussain, and Al-Ameen found that bioreactor landfills with leachate recirculation are superior to sanitary landfills at removing organic matter [9]. The amount of leachate and chemical composition, as well as the distance of the pollutant from the source of water, will affect the pollution level [10].…”
Section: Introductionmentioning
confidence: 99%
“…Complex physical, chemical, and biological processes occur within landfills. Leachate with a substantial amount of pollutants and landfill gas are continually generated in landfills for a very long time [12,13]. e treatment of leachate remains an important environmental issue.…”
Section: Introductionmentioning
confidence: 99%
“…Landfilling is a commonly used MSW management method all around the world [1,2]. Due to the biochemical reaction of degradable components in MSW, the releasing of polluted leachate and landfill gas will be a long-term process that may take years even decades [3][4][5][6]. Therefore, it is of great necessity to reduce landfill emissions so as to avoid long-term environmental risks [7].…”
Section: Introductionmentioning
confidence: 99%